2016
DOI: 10.1111/mmi.13573
|View full text |Cite
|
Sign up to set email alerts
|

A PTS EII mutant library in Group A Streptococcus identifies a promiscuous man‐family PTS transporter influencing SLS‐mediated hemolysis

Abstract: Summary The group A streptococcus (GAS, Streptococcus pyogenes) is a Gram-positive human pathogen that must adapt to unique host environments in order to survive. Links between sugar metabolism and virulence have been demonstrated in GAS, where mutants in the phosphoenolpyruvate-dependent phosphotransferase system (PTS) exhibited Streptolysin S (SLS)-mediated hemolysis during exponential growth. This early onset hemolysis correlated with an increased lesion size and severity in a murine soft tissue infection m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 39 publications
1
49
0
Order By: Relevance
“…Streptolysin S (SLS), a GAS toxin that lyses host tissues and blood cells, was shown to be under the influence of the PTS, as a PTS-null (Δ ptsI ) mutation led to earlier SLS activity as compared to the parental strain MGAS5005 (Gera et al, 2014 ). We screened an annotated EIIC mutant library in a previous study, and discovered 7 out of 14 EIIC mutants that had earlier hemolysis as compared to MGAS5005 (Sundar et al, 2017 ). We carried out this screen in an effort to determine if the lack of utilization of a particular PTS carbon source was responsible for the dysregulation of timely SLS-mediated hemolysis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Streptolysin S (SLS), a GAS toxin that lyses host tissues and blood cells, was shown to be under the influence of the PTS, as a PTS-null (Δ ptsI ) mutation led to earlier SLS activity as compared to the parental strain MGAS5005 (Gera et al, 2014 ). We screened an annotated EIIC mutant library in a previous study, and discovered 7 out of 14 EIIC mutants that had earlier hemolysis as compared to MGAS5005 (Sundar et al, 2017 ). We carried out this screen in an effort to determine if the lack of utilization of a particular PTS carbon source was responsible for the dysregulation of timely SLS-mediated hemolysis.…”
Section: Introductionmentioning
confidence: 99%
“…We carried out this screen in an effort to determine if the lack of utilization of a particular PTS carbon source was responsible for the dysregulation of timely SLS-mediated hemolysis. There was no carbohydrate whose metabolism was commonly effected in all 7 EIIC mutants which displayed early hemolysis (Sundar et al, 2017 ). However, all of these EIIs do appear in the CcpA regulon (DebRoy et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although both MGAS2221 and HSC5, the strain used in the aforementioned study (Kietzman & Caparon, 2009), both contain the sagA cre site we identified, the area upstream of the cre site is quite divergent for the two strains which could explain the differential in vivo binding results. It has been shown that the manLMN operon and the β-glucoside PTS (Table 3), which we identified herein as being directly and indirectly regulated by CcpA respectively, impacts streptolysin production (Braza et al, 2020, Sundar et al, 2017 suggesting that CcpA may regulate streptolysin S production both directly and indirectly. In concert with our data, CcpA was identified as binding in vivo to the gene encoding suilysin, the pore-forming toxin of S. suis, (Willenborg et al, 2014) and to bind in vitro to the sagA promoter of S. anginosus (Bauer et al, 2018).…”
Section: Discussionmentioning
confidence: 56%
“…Because PTSs are central to energy metabolism and unique to bacteria, the system components have been suggested as suitable drug targets [ 20 ]. Interestingly, nature has already provided a validation of this concept—recent studies have demonstrated Man-PTS as a major receptor of class II bacteriocins (natural bactericidal peptides) [ 21 , 22 ]. So far, a number of three-dimensional structures of cytoplasmic components of the mannose-PTS have been determined both by X-ray and NMR methods.…”
Section: Introductionmentioning
confidence: 99%